Gentrification in Cartagena de Indias – Colombia: The case of the La Boquilla - de Cássia Gregório de Andrade, Rita [UNESP]; Góes, Eda Maria [UNESP] (Universidade Federal de Goias, 2023)
We analyze the use of gentrification in a coastal area of the city of Cartagena de Indias, the Corregimiento de La Boquilla. Our aim is to problematize the use of this concept, in the context of the displacement of the resident population and its replacement by tourist enterprises. We did a bibliographic review, survey of documentary information; fieldwork observations; photographic records and conducting interviews. Gentrification in La Boquilla, with content and hygienist, is far from the original meaning of this concept.
Gentrificación en Cartagena De Indias – Colombia – el caso de La Boquilla
Gentrificação em Cartagena de Índias – Colômbia: O caso de La Boquilla
Keywords: Cartagena de Indias; Gentrification; La Boquilla; Tourism